Mechanisms of transverse cracking induced by adjacent ply matrix cracks in composite laminates - Carrère, Nicolas; Doitrand, Aurélien; Conan, Mathilde; Martin, Eric (Comptes Rendus. Mécanique)
Cracking in composite laminates containing θ-plies adjacent to 90° plies is studied experimentally and numerically using the coupled criterion and finite element calculations. Different damage mechanisms are considered, namely transverse cracking in 90°, cracking in θ-plies, or debonding between adjacent misoriented plies. The influence of the stacking sequence on the damage mechanism sequence is investigated. Experimental observations of the composite edge under tensile loading evidence θ-ply cracking (i) at an imposed strain level much larger than first transverse cracking in 90° ply for a sufficiently large orientation mismatch between adjacent plies or (ii) at a similar imposed strain level if the mismatch angle between two adjacent plies is small. The latter phenomenon may be mitigated by the presence of a 0° ply between the 90° and the θ-plies.These conclusions are supported by numerical simulation of the experimentally observed damage mechanisms, evidencing a change in the damage mechanism sequence depending on the θ-ply misorientation. The numerical simulations also highlight that debonding between adjacent plies may occur as it becomes more favorable that adjacent ply crack re-initiation for sufficiently large adjacent ply mismatch angle.